2001
DOI: 10.1094/phyto.2001.91.5.477
|View full text |Cite
|
Sign up to set email alerts
|

Probabilities for Profitable Fungicide Use Against Gray Leaf Spot in Hybrid Maize

Abstract: Gray leaf spot, caused by the fungus Cercospora zeae-maydis, causes considerable yield losses in hybrid maize grown in the north-central United States and elsewhere. Nonchemical management tactics have not adequately prevented these losses. The probability of profitably using fungicide application as a management tool for gray leaf spot was evaluated in 10 field experiments under conditions of natural inoculum in Iowa. Gray leaf spot severity in untreated control plots ranged from 2.6 to 72.8% for the ear leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 17 publications
3
34
0
6
Order By: Relevance
“…Earlier reports suggested that the efficacy of propiconazole for disease control in several crop plants against various diseases. Propiconazole spray significantly reduced anthracnose of strawberry (Smith and Black, 1991), grey leaf spot of maize (Munkvold et al, 2001) and fungal leaf spots of rye grass (Koelsch et al, 1995). The fungicide propiconazole was the most important groups of fungicides (Baldwin and Rathmell, 1988).…”
Section: Effect Of Soil Drenching On Wilt Incidencementioning
confidence: 99%
“…Earlier reports suggested that the efficacy of propiconazole for disease control in several crop plants against various diseases. Propiconazole spray significantly reduced anthracnose of strawberry (Smith and Black, 1991), grey leaf spot of maize (Munkvold et al, 2001) and fungal leaf spots of rye grass (Koelsch et al, 1995). The fungicide propiconazole was the most important groups of fungicides (Baldwin and Rathmell, 1988).…”
Section: Effect Of Soil Drenching On Wilt Incidencementioning
confidence: 99%
“…The posterior distribution describes the knowledge about the parameter after the data are collected. Following Munkvold et al (2001), we present the probability that the yield gain from a treatment exceeded the GT at each of the four soybean prices. Given an appropriate choice of prior distributions, the posterior distribution of the difference in yield is a rescaled t-distribution (Box and Tiao 1973).…”
Section: Inmentioning
confidence: 99%
“…Nos últimos anos, o uso de fungicidas foliares em lavouras comerciais de milho tem aumentado de forma significativa nas principais regiões produtoras do Brasil e no mundo (Adee et al, 2005;Cunha et al, 2010;Juliatti et al, 2007;Munkvold et al, 2001;Pinto et al, 2004;Shah & Dillard, 2010). Tem sido bastante discutida e divulgada a existência de efeitos fisiológicos dos fungicidas do grupo das estrobilurinas em diversas culturas, inclusive no milho.…”
Section: Discussionunclassified
“…Algumas empresas têm divulgado o uso desses fungicidas para o manejo de estresses bióticos e abióticos em diversas culturas, sugerindo um potencial aumento de produtividade mesmo na ausência de doenças no campo (Rava, 2002;Wise & Mueller, 2011). No entanto, não se conhecem resultados de pesquisa quantificando esse potencial aumento da produtividade em milho advindo da utilização dos fungicidas estrobilurinas, e a magnitude dos benefícios econômicos desses fungicidas tem sido bastante questionada por parte de alguns patologistas de milho (Munkvold et al, 2001).…”
Section: Discussionunclassified